AN INFORMATION COMPETENCE AS A COMPONENT OF LINGUISTIC AND DIDACTIC TRAINING OF FUTURE TEACHERS OF THE UKRAINIAN LANGUAGE IN THE CRIMEAN-TATAR PRIMARY SCHOOL (Journal of Information Technologies in Education (ITE), 2015)
The article is deals to the problem of formation of information competence in the context of the linguistic and didactic training of future teachers of the Ukrainian language in primary school in terms of bi- and for trilingual learning environment. Also is exposed the concept of «lingodidactic competence of future teachers of the Ukrainian language in primary school with the Crimean Tatar language of instruction» and «information competency». Proposed the ways of creation of information competence as an integral interdisciplinary in structure linguistic and didactic training of students of the specialty «A primary education».     The solution to the problem of formation of information competence reflects the pedagogical, linguistic and didactic and methodological feasibility of using information technology on practical, seminar and lecture classes professionally oriented disciplines cycle. Based on the principle of interdisciplinary training of future teachers allocated to those disciplines in the study and assimilation of which management is the use of information and communication technologies.These include «Teaching methods of teaching the Ukrainian language in the primary school»,«Teaching methods the Crimean Tatar language in the primary school», «Foundations of bilingual teaching languages (Ukrainian, Crimean Tatar)», «Methodology of educational translation (Ukrainian/Crimean Tatar)» to the specialty «A primary education» in higher pedagogical institution.
Keywords: a system of professional training; a linguistic and didactic competence of the teacher of primary classes; an information technology training; e-learning; e-training material; electronic manual; electronic bilingual dictionaries; electronic library